Effect of spark plasma sintering process on the microstructure and mechanical properties of Nano crystalline hydroxyapatite ceramics prepared by hydrolysis in polyol medium - Mechay, Abderrahmen; Elfeki, Hafed; Schoenstein, Fréderic; Tétard, Florent; Jouini, Noureddine (International Journal of Advanced Chemistry, 2014)
The aim of the study was to investigate the role of microstructure and porosity on the mechanical behaviour of sintered hydroxyapatite synthesized by polyol process. This process describes a new approach for the synthesis of hydroxyapatite nanoparticles, which involves precipitation and hydrolysis reactions conducted in polyol medium. In the present work a non-conventional technique, spark plasma sintering, was used to consolidate such nanocrystalline apatites at non-conventional, very low temperatures (T < 300°C) so as to preserve the surface hydrated layer present on the nanocrystals. The hydroxyapatite nanoparticles have been successfully conducted by spark plasma sintering process, resulting in a dense HA compacts. Besides, the sintering behaviour of hydroxyapatite powders at different temperatures ranging was studied. The microstructure, Vickers microhardness, nanoindentation and density are described. Finally, the resulting mechanical properties determined on the microwave sintered samples (E = 136 ±4 GPa, HV = 8.2 GPa, and KIC= 1.6 ±0.03 MPa m1/2) are significantly higher than those usually reported in the literature, whatever the sintering process, and could allow the use of hydroxyapatite for structural applications. Keywords: Hydroxyapatite; Polyol; Spark Plasma Sintering; Mechanical Properties.